The Cocoa Commodity Diversification in Supporting Agrotourism Development in Pekon Suka Marga, West Lampung Regency, Lampung Province - Mustofa, Asep Nurul Ajiid; Pratami, Mentari; Syahputra, Andi; Harianja, Rahmattullah; Yunira, Eka Nur’azmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2023)
Cocoa is Indonesia's leading plantation product because Indonesia's cocoa production is the third largest in the world. One of the cocoa center areas is Suka Marga village, Suoh sub-district, West Lampung district. Suka Marga Village is also included in the Bukit Barisan National Park which has a total area of 313,572.48 hectares. Meanwhile, the largest cocoa production in West Lampung Regency, precisely in Suka Marga Village, even now Suka Marga Village is designated as an Agrotourism area. The results of cocoa processing have not yet characterized the village's superior products because they are still not optimal in utilizing commodity products and the lack of knowledge of village communities in managing cocoa commodity products. The plans that have been scheduled and implemented have reflected the collaboration and openness between the village apparatus and the community which encourages the creation of development transparency, especially in developing the potential of cocoa commodities in supporting the development of agro-tourism with the icon of processed cocoa products as economic added value for regional development in Pekon Suka Marga.